Trends in green infrastructure studies in Brazil - Santos, Maria Fernanda Nóbrega dos; Enokibara, Marta; Fontes, Maria Solange Gurgel de Castro (National Journal of City Management, 2020)
Due to the relevance that green infrastructure (GI) subject has reached in recent years, as an interdisciplinary research topic within urban planning, the present study addresses a literature review on the subject in Brazil. The study aimed to present an overview of the main research trends in GI, based on the analysis of the keywords used on the papers published in indexed Brazilian journals. The research scope included papers published until the year of 2018 with GI (and its variations) as a keyword. The research was carried out on Google Scholar and 64 papers were identified. As results, 295 keywords were employed in the papers and 168 different terms were classified. The most used keywords in association with GI were: “sustentabilidade” [sustainability], “desenho ambiental” [environmental design], “drenagem urbana” [urban drainage], “ecologia urbana” [urban ecology], and “paisagem urbana” [urban landscape]. Regarding the papers’ focus, most can be classified as case studies: design and guidelines proposed for new and renewal areas, as well as the analysis of already build projects. The topic “drenagem urbana” [urban drainage] stands out as a cross-sectional research area, related to the other main themes within GI. On the other hand, the topic “paisagem urbana” [urban landscape] can be considered a more delimited research area. Furthermore, it is expected that through this overview, the present study can contribute to future publications within GI, in order to support the authors to choose the keywords that best communicate with their target audience.